PENGARUH KECERDASAN EMOSIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Ariyanto, Dwi -; Triastity, Rahayu - (Universitas Slamet Riyadi, 2011)
ABSTRACT This study aims to (1) analyze the significance of the influence of emotional intelligence on the performance of nurses, (2) analyzing the significance of the influence of organizational commitment on the performance of nurses, (3) analyzing the significance of the influence of work motivation on the performance of nurses, (4) analyze the performance of emotional intelligence nurse moderated motivation, (5) analyze the performance of the organization's commitment to nurses who work motivation moderated. This study is a population using all nurse respondents Rahayu Hospital Panti Purwodadi in District Purwodadi Grobogan some 130 people. Techniques of data collection using questionnaires through validity and reliability. Regression test requirements using the classical assumption test. Analysis using multiple regression analysis and regression testing moderating the absolute value of the difference. Results of this study indicate that (1) emotional intelligence significantly influence the performance of nurses, (2) organizational commitment have a significant effect on the performance of nurses, (3) Motivation significant effect on the performance of nurses, (4) Work motivation moderate the impact of emotional intelligence on the performance of nurses, (5) work motivation moderate the influence of organizational commitment on the performance of nurses. Keywords: emotional intelligence, organizational commitment, job motivation, nurse’s performance.